Jak2 negative polycythemia vera- a diagnostic dilemma - DR.E.DHIVYA; DR.K.H.NOORUL AMEEN (International Journal of Pharma and Bio Sciences, 2017)
Polycythemia vera or Osler-Vaquez disease is a rare myeloproliferative disorder characterised as a malignant,neoplastic and panhyperplastic marrow disorder with increased absolute red cell mass along with an increase in both leukocyte and platelet production.Though it can occur in any age group, it is more common above the age of 60 years and quite rare under 30 years of ​age.About 95% of the individuals with polycythemia vera test positive for JAK2 mutation.JAK2 or Janus Kinase is a tyrosine kinase gene that helps in the ​signalling of the cytokine receptors and unchecked proliferation leads to the increased cellular production. We report a patient belonging to the younger age group and diagnosed to have JAK2 negative polycythemia ​vera.There are various guidelines proposed for the diagnosis of polycythemia vera but the subsequent discovery of JAK2 mutation allowed revised diagnostic criteria.This condition is much more challenging in terms of diagnosis and response to treatment as JAK2 mutation was negative.The patient was started on hydroxyurea-a cytoreductive drug and underwent phlebotomy and is on regular follow-up.